The Role of the Prosecutor's Office in Safeguarding State/Regional Assets as an Efforts to Prevent Corruption in Indonesia - Ricky Setiawan Anas; Faisal Santiago (International Journal of Law, Crime and Justice, 2024)
The office of the prosecutor, in its efforts to combat corruption, needs to collaborate with the Attorney General's Office, the High Prosecutor's Office, and the District Attorney's Office to protect and reclaim state financial losses. The research aims to understand the role of the prosecutor's office in asset recovery to prevent corruption crimes in Indonesia. The research method used is normative juridical. The findings indicate that asset recovery starts from monitoring the wealth of potential suspects and is followed by an investigation. The government should put in place measures to prevent crime, such as verifying the identities of public officials and their families and monitoring their bank accounts to stop the laundering of criminal proceeds. In 2022, the prosecutor's office successfully recovered IDR 39.207 trillion and has recovered by 2024 of IDR 23 trillion. The conquest demonstrates the effectiveness of the prosecutor's office challenges, including a lack of witnesses, limited resources, lengthy audit processes, inadequate indictment applications, differences in understanding between prosecutors and judges, and difficulties in asset seizure and tracking.